(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the philosophical features and general qualities of sufism and futuwat doctrine. Also, the article has scientifically and theoretically researched the altruistic content of humanistic ideas such as tolerance, bigotry, justice, modesty, and hard work in the development of an enlightened society, which are characteristic of universal human values, based on futuvvat and mystical views.